Videoconferencing fatigue and online student engagement among Filipino senior high school students: A mixed methods study - Dacillo, Mikaela Jasmin F.; Dizon, Jhoana Katrina M.; Ong, Earl Johann T.; Pingol, Althea Mae L.; Cleofas, Jerome V. (Frontiers in Education, 2022)
The ubiquity of online classes during the COVID-19 pandemic induced the widespread use of videoconferencing applications. However, the prolonged use of these applications can lead to videoconferencing fatigue. Drawing from an online survey sample of 215 senior high school students from a selected private university in Manila, Philippines, this mixed methods study examines videoconferencing fatigue and its relationship with online student engagement (OSE) during the COVID-19 pandemic. The quantitative strand utilized a cross-sectional design. The constructs were measured using the Zoom Exhaustion & Fatigue Scale and Online Student Engagement Scale. Bivariate and multivariate statistical analysis was used to determine the significance of the relationships between variables. The qualitative strand utilized a descriptive design. Narrative data were collected through an open-ended survey question and analyzed using content analysis. Quantitative results indicate moderate to high levels of videoconferencing fatigue among student respondents. Moreover, higher levels of OSE were observed among those who endured higher visual fatigue and attended videoconferences more days a week. Qualitative findings demonstrate various manifestations of videoconferencing fatigue among students and relate it with decreased energy to perform academic tasks and learning absorption. However, the qualitative analysis also reveals students' perceived need for videoconferencing to learn online. The nuanced insights from both strands highlight that despite their perceived negative impacts of videoconferencing, students had to tolerate visual videoconferencing fatigue in order to engage meaningfully in online classes.